Penggunaan Media Pembelajaran terhadap Keterampilan Berpikir Kritis IPS Siswa Sekolah Dasar - Amelia Putri Wulandari; Annisa Annisa; Tin Rustini; Yona Wahyuningsih (Departement of Mathematics Education, 2023)
This study aims to determine the use of learning media in improving students' critical thinking skills in social studies learning in the Higher Class. This type of research is a literature study with a descriptive qualitative research type with library research from research journals in previous years to be used as research subjects. This research is sourced from several journals that are relevant to the topic of the discussion on Learning Media on Social Studies Critical Thinking Skills for Elementary School Students. The results obtained are the use of learning media is very effective and efficient in its use, depending on what learning media is used and the selection of learning media in accordance with the provisions of the social studies material being taught adds to the usefulness of the use of learning media.